Self-regulated Learning Among Undergraduate College Students with Parental Divorce - Rohman Hikmat; Yanti Hermayanti; Atlastieka Praptiwi; Azalia Melati Putri (JENDELA NURSING JOURNAL, 2022)
Background: Parental divorce can cause psychological problem and disturbances in communication that have an impact on the student learning process. Thus, good self-regulation in the learning process is needed to keep students focused on achieving learning goals.Purpose: This study aims to identity the self-regulation of undergraduate college students who experienced parental divorce.Methods: Quantitative descriptive study was conducted in this study by using accidental sampling technique with a response rate of 34.65% (n=113) via online survey. Data was collected using the Self-Regulated in Online Learning Questionnaire (SOL-Q) and analyzed using univariate descriptive analysis.Results: The results showed that 52.2% of students with divorced parents had high self-regulation in learning and 47.8% of students had low self-regulation in learning. On the other hand, some of the students with parental divorce issues were in the low category on several aspects such as metacognitive skills (51.3%), persistence (52.2%), environmental management (49.6%), and seeking help (47.8%); and more than one third of respondents (38.1%) are also in the low category on the time management component.Conclusion: This study shows that respondents with high and low self-regulated learning are almost in equal proportion. The nursing profession can contribute to various collaborative efforts to improve student self-regulation in learning to improve students' psychological well-being and optimize their learning outcomes while studying in college.